Arabidopsis thaliana homeobox 12 (ATHB12), a homeodomain‐leucine zipper protein, regulates leaf growth by promoting cell expansion and endoreduplication. Issue 1 (3rd September 2014) - Hur, Yoon‐Sun; Um, Ji‐Hyun; Kim, Sunghan; Kim, Kyunga; Park, Hee‐Jung; Lim, Jong‐Seok; Kim, Woo‐Young; Jun, Sang Eun; Yoon, Eun Kyung; Lim, Jun; Ohme‐Takagi, Masaru; Kim, Donggiun; et al.
Summary Arabidopsis thaliana homeobox 12 (ATHB12), a homeodomain‐leucine zipper class I (HD‐Zip I) gene, is highly expressed in leaves and stems, and induced by abiotic stresses, but its role in development remains obscure. To understand its function during plant development, we studied the effects of loss and gain of function. Expression of ATHB12 fused to the EAR‐motif repression domain (SRDX) – P35S::ATHB12SRDX (A12SRDX) and PATHB12::ATHB12SRDX – slowed both leaf and root growth, while the growth of ATHB12‐overexpressing seedlings (A12OX) was accelerated. Microscopic examination revealed changes in the size and number of leaf cells. Ploidy was reduced in A12SRDX plants, accompanied by decreased cell expansion and increased cell numbers. By contrast, cell size was increased in A12OX plants, along with increased ploidy and elevated expression of cell cycle switch 52s (CCS52s), which are positive regulators of endoreduplication, indicating that ATHB12 promotes leaf cell expansion and endoreduplication. Overexpression of ATHB12 led to decreased phosphorylation of Arabidopsis thaliana ribosomal protein S6 (AtRPS6), a regulator of cell growth. In addition, induction of ATHB12 in the presence of cycloheximide increased the expression of several genes related to cell expansion, such as EXPANSIN A10 (EXPA10) and DWARF4 (DWF4). Our findings strongly suggest that ATHB12 acts as a positive regulator of endoreduplication and cell growth during leaf development.